2004
DOI: 10.1242/jeb.00897
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of two types of hemopexin-like protein in medaka and differences in their affinity to heme

Abstract: Full-length cDNA clones encoding two types of hemopexin-like protein, mWap65-1 and mWap65-2, were isolated from the HNI inbred line of medaka Oryzias latipes. The deduced amino acid sequence of mWap65-2 resembled mammalian hemopexins more closely than that of mWap65-1. Histidine residues required for the high affinity of hemopexins for hemes were conserved in mWap65-2, but not in mWap65-1. Surprisingly, mWap65-1, but not mWap65-2, showed heme-binding ability as revealed by hemin-agarose affinity chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
5
41
3
1
Order By: Relevance
“…This gene set has also been shown to be induced in response to immunological stimulus using LPS and hypoxia in C. auratus (Kikuchi et al, 1997;Gracey et al, 2001). However, there is no elevation in the expression of either of the two wap65 isoforms to induction by LPS in O. latipes (Hirayama et al, 2004) or to environmental temperature increases in O. latipes and T. rubripes (Hirayama et al, 2003). Indeed, so far, the correlation of increased expression levels of wap65 with increased environmental temperature have only been identified in the Cypriniformes, specifically the wap65-1 isoform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene set has also been shown to be induced in response to immunological stimulus using LPS and hypoxia in C. auratus (Kikuchi et al, 1997;Gracey et al, 2001). However, there is no elevation in the expression of either of the two wap65 isoforms to induction by LPS in O. latipes (Hirayama et al, 2004) or to environmental temperature increases in O. latipes and T. rubripes (Hirayama et al, 2003). Indeed, so far, the correlation of increased expression levels of wap65 with increased environmental temperature have only been identified in the Cypriniformes, specifically the wap65-1 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Wap65-2 has a much more restricted tissue distribution (mainly liver), compared to wap65-1, which is present in multiple tissues in O. latipes and Takifugu (Hirayama et al, 2003;2004). In spite of the presence of the two conserved histidine residues proposed to be essential for haem binding, other fish orthologues of Wap65-2, which also contain these residues, do not show an affinity for haem (Hirayama et al, 2004). There is sufficient conservation of gene sequence between H. antarcticus wap65-2 and O. latipes wap65-2 to suggest that the two genes are functional orthologues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oligosaccharides attached to this protein promote glycoprotein folding, contribute to proteinÁprotein interactions, regulate other ligand recognition processes, and stabilize the protein, making it resistant to proteolysis (Helenius and Aebi 2004;Ohtsubo and Marth 2006). Up to now, the role of the oligosaccharide in this glycoprotein has been unclear; however, Satoh et al (1994) reported that N-linked glycosylation is an essential part of the high affinity of human hemopexin for heme, and Hirayama et al (2004) reported that fish Wap65 binds heme.…”
Section: Discussionmentioning
confidence: 99%
“…Wap65 was first detected as a glycoprotein in the plasma of goldfish (Kikuchi et al 1993) and has since been identified in medaka (Oryzias latipes), channel catfish (Ictalurus punctatus), swordtail fish (Xiphophorus hellerii), and fugu (Takifigu rubripes) (Kikuchi et al 1995;Kinoshita et al 2001;Hirayama et al 2003Hirayama et al , 2004Nakaniwa et al 2005;Aliza et al 2008). Teleost Wap65 shares significant sequence identity with mammalian hemopexin and has been suggested to play roles in iron homeostasis, antioxidant activity, bacteriostatic defense, nerve regeneration, transfer of heme, and the expression of genes known to promote cell survival (Delanghe and Langlois 2001).…”
Section: Introductionmentioning
confidence: 99%